Modification of Secondary Dyes in Gram Staining Protocol to Increase The Diagnostic Accuracy of Bacterial Vaginosis Infections - Risqia, Rahma Maulida; Maryani, Maryani; Murasmita, Alamanda (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: The diagnosis of bacterial infection can only be made by gram stain with patient information. One of the problems with gram staining is that the resulting microscopic images look dim, making them prone to misinterpretation. Researchers conducted a study on modifying secondary dyes in gram staining to improve the accuracy of the diagnosis of Bacterial vaginosis infections.Methods: This research is a laboratory experimental study with a cross sectional approach. The sample of this study consisted of anaerobic gram-negative rods on vaginal swabs of patients diagnosed with Bacterial vaginosis at Dr. Moewardi Hospital and Sebelas Maret University Hospital during March to July 2022. The samples were then treated in the form of gram staining with different secondary dyes and then compared.Results: The color intensity of anaerobic gram-negative rod bacteria samples treated with gram staining using fuchsin secondary dye appeared to be stronger than safranin secondary dye. Likewise, the resulting focus looks clearer. The diagnostic test showed that modification of secondary dyes in gram staining by substituting safranin into fuchsin increased the color intensity and focus of preparations Conclusion: Modification of secondary dye on gram staining by replacing secondary dye of safranin to fuchsin can improve the quality of gram staining results on anaerobic gram negative bacteria thereby increasing the accuracy of diagnosis and treatment given.